Laminated Composite on the Basis of Plasma Modified PTFE Films and Thin Aluminum Layers - Yablokov, M.; Gilman, A.; Kechek'yan, A.; Kuznetsov, A. (International Conference on Plasma Surface Engineering, 2013)
Not available